Model Pengembangan Usaha Wisata Kuliner Oepoi Dalam Masa Pandemi Covid-19 Di Kota Kupang: Model Pengembangan Usaha Wisata Kuliner - Lawalu, Emiliana Martuti; Ketmoen, Adrianus; Taneo, Brian (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Timor, 2023)
Covid 19 caused economic instability of society. In this case is small and middle business sector. It was dealing with the decline of people’s purchasing power because of social distancing and large-scale social restriction policy. The results are happened the termination of employment, the decrease in sale turnover and even close the business. For small and middle business pertaining culinary tour, naturally it encountered the problem because of being empty buyers for their culinary products. The goal of this study is to explore business delineation of culinary tour in Oepoi Kupang and such business strategy in responding Covid 19. While the method used for gaining the goal are qualitative one, such as interview, participant observation, and literature review. The results of study denoted that culinary business are dominated by settler or Javanese entrepreneur, and take charge of the stall at fee IDR 1.500.000 per mounth. Business delineation was dealing with income declining because of government large-scale restriction policy. Even so, the entrepreneurs steady to survive in running the business. The strategi they make to maintain the busniss is selling by E-commerse and digital marketing. It is importan strategic choice to the income improvement and give the easiness to consumer in shoping. Moreover as entrepreneurs they need to improve for the good service through products quality, hygiene guarantee, products safety, and service quality improvement.